2004
DOI: 10.1007/s00421-004-1225-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural activation of the triceps surae is impaired following 2�weeks of immobilization

Abstract: The purpose of this study was to investigate the effect of 2 weeks of ankle joint immobilization on triceps surae neural activation, with particular emphasis on the potential differences between the monoarticular soleus and the biarticular gastrocnemius muscles. Seventeen male volunteers were divided into the immobilized group (IG, n = 8) and the control group (CG, n = 9). Elastic adhesive bandages and an ankle stabilization orthosis were used to immobilize the ankle joint only. The plantar flexor torque obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
39
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 30 publications
8
39
3
1
Order By: Relevance
“…The results of the present study agree with those of prior ULLS studies (Clark et al, 2006;de Boer et al, 2007;Seynnes et al, 2010) in that we also found no significant change in central activation (pϭ0.085). Hence, the changes in maximal activation of planter flexor muscles following "ULLS" seem at odds with what has been observed in the aforementioned unloading or disuse paradigms (Duchateau, 1995;Lambertz et al, 2001;Kawakami et al, 2001;Gondin et al, 2004).…”
Section: The Effects Of Ullsmentioning
confidence: 46%
See 1 more Smart Citation
“…The results of the present study agree with those of prior ULLS studies (Clark et al, 2006;de Boer et al, 2007;Seynnes et al, 2010) in that we also found no significant change in central activation (pϭ0.085). Hence, the changes in maximal activation of planter flexor muscles following "ULLS" seem at odds with what has been observed in the aforementioned unloading or disuse paradigms (Duchateau, 1995;Lambertz et al, 2001;Kawakami et al, 2001;Gondin et al, 2004).…”
Section: The Effects Of Ullsmentioning
confidence: 46%
“…Regarding activation capacity, a decrease has been observed consistently after spaceflight (Lambertz et al, 2001), bed rest (Duchateau, 1995;Kawakami et al, 2001), or casting (Gondin et al, 2004). On the other hand, in all investigations utilizing the "ULLS model," the decrease in voluntary activation observed after ULLS failed to reach significance (Clark et al, 2006;de Boer et al, 2007;Seynnes et al, 2010).…”
Section: The Effects Of Ullsmentioning
confidence: 95%
“…In early stages of immobilization, reduced neural drive accounts for a large portion of the decrease in plantar flexor strength loss (Duchateau 1995;Gondin et al 2004); therefore, it is important to develop effective countermeasures to neuromuscular deconditioning. With both potential ipsilateral and contralateral effects, a tendon vibration program might be beneficial for individuals who are hypoactive or immobilized, and not candidates for whole-body vibration.…”
Section: Introductionmentioning
confidence: 99%
“…So, after repair, patients need to maintain about six-week fixation using ultra-sling for arms, in order to limit active motion [28]. However, it is said that such a fixation causes muscular activity in muscles surrounding the repaired portion and brings about changes in Cuff Repair [14]. If muscular activity is reduced, it is closely related to muscle fatigue and this affects median frequency value because EMG spectrum can be shifted if there are changes in the width in measuring EMG [29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who received a rotator cuff muscle repair indicated that muscular activity weakened in lower extremities even with no weight bearing because the surgical site was fixated and it brought about changes in myotility [14], and Downie and Miller [15] reported that after repair, tendon and muscular atrophy increased the fatigue in the surrounding muscles over time.…”
Section: Introductionmentioning
confidence: 99%